Application Research of BP Neural Network Algorithm in Power Line Loss Calculation. Issue 1 (January 2022) - Dai, Su; Ma, Yunlong; Wang, Kai; Liu, Bowen; Liu, Changming
Abstract: In recent years, it is still a difficult problem to calculate the line loss of distribution system. The main reason is that China's power system data is not perfect, the components are huge, the management function does not exist, the network structure is directly connected. Therefore, reducing the loss rate of power system has become an urgent problem for energy companies to solve. Developing effective methods for line loss reduction evidence and line loss assessment requires careful calculation and analysis of line loss, which ultimately contributes to and guides line loss management.